2023
DOI: 10.1186/s13034-023-00592-0
|View full text |Cite
|
Sign up to set email alerts
|

The gender gap in adolescents’ emotional and behavioural problems in Georgia: a cross-sectional study using Achenbach’s Youth Self Report

Abstract: Background Adolescents, particularly girls, are vulnerable to mental health disorders. Knowledge about young people’s mental health in Eastern European countries is limited. This study is the first to investigate adolescents’ self-reported emotional and behavioural problems in Georgia from a public mental health perspective. Methods This study utilized Achenbach’s Youth Self-Reported syndrome scales among 933 adolescents studying from grades 7–12 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…According to an established review, it was illustrated that males were more expressive and aggressive than females for externalizing their problems whereas females tended to internalize their problems, which lead to higher anxiety, depression, and withdrawal behaviors, corresponding to higher YSR scores. 40 An additional confounding factor regarding behavioral changes in Lebanese adolescents was found to be the type of schooling. Our results demonstrated a novel comparison that showed higher levels of YSR scores (Table 4).…”
Section: Multivariable Analysesmentioning
confidence: 99%
“…According to an established review, it was illustrated that males were more expressive and aggressive than females for externalizing their problems whereas females tended to internalize their problems, which lead to higher anxiety, depression, and withdrawal behaviors, corresponding to higher YSR scores. 40 An additional confounding factor regarding behavioral changes in Lebanese adolescents was found to be the type of schooling. Our results demonstrated a novel comparison that showed higher levels of YSR scores (Table 4).…”
Section: Multivariable Analysesmentioning
confidence: 99%
“…Several studies have claimed to detect poorer mental health in girls, especially those that do not have adequate social support [12]. Reports during the pandemic have estimated that girls experience more psychological distress, less life satisfaction, and higher results on syndrome and internalizing broadband scales [13,14]. Vučenović et al [15] found that amid the COVID-19 crisis, girls have reported higher levels of depression, while others state their symptoms are more severe [16].…”
Section: Introductionmentioning
confidence: 99%